A Growing Gen-Z Audience For Capital Markets: The Impact Of Knowledge, Motivation And Minimum Capital - Afisa, Ulya Noor; Fasihah, Lu'lu'ul; Amaroh, Siti (Universitas Bunda Mulia, 2024)
According to data from the Indonesian Central Securities Depository (KSEI), as of August 2023, Gen-Z accounted for 57.04% of all 11.5 million investors, making it one of the largest investment groups in the country's capital market. Because of this, the author is curious to find out which capital market products pique Gen-Z's interest in making capital market investments. The purpose of this study is to examine how Gen-Z's interest in capital market investing is influenced by investment knowledge, investment motivation, and minimum capital requirements. The 98 individuals in the Gen-Z group who were part of the Central Java Province population comprised the study's population. The approach used to acquire the data was the distribution of questionnaires. The study's findings indicated that Gen-Z's interest in investing in the capital market was positively and significantly impacted by investment knowledge, investment desire, and minimal capital. Gen Z should learn more about finance and investing to further increase investment knowledge. They should also be given attractive offers such as experience gained and investment benefits to increase investment motivation. Meanwhile, to start investing, Gen Z only needs to spend IDR 100,000 in capital.